The Impact of Pro-Inflammatory Cytokines on the Clinical Manifestations and Disease Progression of Spondyloarthritis: a Narrative Review - Sari, Lia Cahya; Sitanggang, Robestri Natalia; Qudsiyyah, Farida (Program Studi Akuntansi IKOPIN, 2025)
Spondyloarthritis (SpA) is a group of inflammatory joint and spine diseases with various clinical manifestations. The classification and diagnosis of SpA are determined based on observations of the sacroiliac joints, hip joints, enthesitis, or the presence of human leukocyte antigen B27 (HLA-B*27). The main clinical manifestations of SpA are inflammatory pain, stiffness, and swelling of the joints and spine. Although the pathogenesis of SpA is not fully understood, genetic and environmental factors can lead to inflammation by producing pro-inflammatory cytokines such as TNF-α and the IL-23/IL-17 axis, which cause dysregulation of immune cells and stromal cells. This review aims to find out the impact of pro-inflammatory cytokines on the clinical manifestations and disease progression of Spondyloarthritis. Pro-inflammatory cytokines, such as TNF-α, IL-17, and IL-23 have an important role in the pathogenesis and progression of Spondyloarthritis. IL-17A stimulates the expression of RANKL and inhibits Wnt signaling, thereby suppressing osteoblast activity, promoting osteoclast differentiation and bone resorption in axSpA and PsA. IL-17 also trigger arthritis, spondylitis, and conjunctivitis in ReA. Increased expression of IL-17, IL-23, and TNF-α due to microbiota activity provides immune cell recruitment and mucosal injury, thus maintaining chronic inflammation in IBD. Pro-inflammatory cytokines have an impact on clinical manifestations of spondyloarthritis by stimulating an inflammatory response in the joints, leading to pain, and influencing disease progression by causing bone and joint tissue destruction. They also contribute to the formation of scar tissue around the joints, reducing mobility and causing significant stiffness in the spine